2020
DOI: 10.3390/children7070075
|View full text |Cite
|
Sign up to set email alerts
|

African American Children’s Diminished Returns of Subjective Family Socioeconomic Status on Fun Seeking

Abstract: Background: Reward sensitivity (fun-seeking) is a risk factor for a wide range of high-risk behaviors. While high socioeconomic status (SES) is known to reduce reward sensitivity and associated high-risk behaviors, less is known about the differential effects of SES on reward sensitivity. It is plausible to expect weaker protective effects of family SES on reward sensitivity in racial minorities, a pattern called Minorities’ Diminished Returns (MDRs). Aim: We compared Caucasian and African American (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 126 publications
(207 reference statements)
2
12
0
Order By: Relevance
“…This is the first paper that documents the differential effects of family income on delayed gratification/delayed discounting of Latino and non-Latino children in the US. Racial and ethnic differences in the effects of family SES are reported for other psychological factors such as inhibitory control [42], fun seeking [27], and impulsivity [28]. The unique contribution of this paper is to enrich the literature on differential effects of family income on delay gratification and delayed discounting which are correlated with a wide range of high-risk behaviors [24,29,30,32,39].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is the first paper that documents the differential effects of family income on delayed gratification/delayed discounting of Latino and non-Latino children in the US. Racial and ethnic differences in the effects of family SES are reported for other psychological factors such as inhibitory control [42], fun seeking [27], and impulsivity [28]. The unique contribution of this paper is to enrich the literature on differential effects of family income on delay gratification and delayed discounting which are correlated with a wide range of high-risk behaviors [24,29,30,32,39].…”
Section: Discussionmentioning
confidence: 92%
“…This study, however, extends this literature to the comparison of Latino We found that while children who live in high-income families have high delayed gratification, this effect is not the same for Latino compared with non-Latino families. Some research studies have shown the differential effects of family income, household income, parental education, and marital status on impulse control [28], inhibitory control [42], and fun seeking [27] by race and ethnicity. As a result, high SES Latino and Black children have high aggression [16], poor school function [21], school bonding [43], and tobacco use [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other ABCD studies, high-SES black children remained at risk of reward dependence. However, white high-SES children had low reward dependencies [ 42 , 67 ]. In other studies, high-SES black children remained at risk of social, emotional, and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…We only tested the MDRs of family income. Previous work had established MDRs of various family SES indicators, such as parental education [ 42 , 67 ]. Future research should test if similar MDRs also apply for other behaviors and time spent on other activities.…”
Section: Discussionmentioning
confidence: 99%